0
$\begingroup$

Hi I have a question related to the treatment effect.

Recently, I am reading literatures on treatment effect and have a question.

In the literatures, we denote the counterfactual outcomes as $Y_1$ and $Y_0$ where $Y_1$ is for the treated and $Y_0$ is for the untreated. Then, the observed outcome is $Y=W\cdot Y_1+(1-W)\cdot Y_0$ where $W$ is the indicator of the treatment.

Here, my first question is whether or not $E(Y_1|W=1)$ and $E(Y|W=1)$ are different?

Second, I found an equation that is as follows: $$ \begin{aligned} E(Y|W=1)-E(Y|W=0) &= E(Y_1-Y_0)\\ &+\{E(Y_1|W=1)-E(Y_1|W=0)\}P(W=0)\\ &+\{E(Y_0|W=1)-E(Y_0|W=0)\}P(W=1) \end{aligned} $$ where P() is the probability function. But, I can't derive the equation.

Please, Help Me! Thank you for your time spent to read this question.

$\endgroup$

1 Answer 1

0
$\begingroup$

To answer your first question, we have $$E(Y | W = 1) = E(W\cdot Y_1 + (1 - W) \cdot Y_0 | W = 1) = E(Y_1 | W = 1)$$ where the last equality follows by the fact that we are allowed to plug in the conditioned value of $W$ when evaluating the conditional expectation, so yes, they are equal. Of course, a similar argument shows that $E(Y | W = 0) = E(Y_0 | W = 0)$. I end up using both of these facts below:

To answer your second question, it seems the expression you wrote down is off by a negative sign. To get the correct expression, the only real trick is to use the law of iterated expectations prudently and to do some light algebra afterwards:

$$ \begin{aligned} E(Y_1) &= E(Y_1 | W = 1)P(W = 1) + E(Y_1 | W = 0) P(W = 0)\\ &= E(Y_1 | W = 1)[1 - P(W = 0)] + E(Y_1 | W = 0) P(W = 0)\\ &= E(Y_1 | W = 1) - \{E(Y_1 | W = 1) - E(Y_1 | W = 0)\} P(W = 0)\\ &= E(Y | W = 1) - \{E(Y_1 | W = 1) - E(Y_1 | W = 0)\} P(W = 0) \end{aligned} $$

$$ \begin{aligned} E(Y_0) &= E(Y_0 | W = 1)P(W = 1) + E(Y_0 | W = 0) P(W = 0)\\ &= E(Y_0 | W = 1)P(W = 1) + E(Y_0 | W = 0) [1 - P(W = 1)]\\ &= E(Y_0 | W = 0) + \{E(Y_0 | W = 1) - E(Y_0 | W = 0)\} P(W = 1)\\ &= E(Y | W = 0) + \{E(Y_0 | W = 1) - E(Y_0 | W = 0)\} P(W = 1) \end{aligned} $$

Now, adding these two equalities together and rearranging, we get

$$ \begin{aligned} E(Y|W=1)-E(Y|W=0) &= E(Y_1-Y_0)\\ &+\{E(Y_1|W=1)-E(Y_1|W=0)\}P(W=0)\\ &-\{E(Y_0|W=1)-E(Y_0|W=0)\}P(W=1) \end{aligned} $$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.